Dampak Kualitas Pelayanan Berbasis Nilai Syariah di Apotek Karya Sehat Purwokerto Terhadap Kepuasan Konsumen - Rizki, Inesya Febrianing; Hardiyanti , Annisa Mufidah; Rismayanti , Rismayanti (Journal of Pharmaceutical and Sciences, 2025)
Sharia-based services can improve consumer satisfaction. The four main principles of Islamic teachings on service are Rabbaniyyah, service, Waqi'iyyah, and Insaniyyah. The high and low quality of service can be determined by consumer behavior, namely Rabbaniyyah, Akhlaqiyyah, Waqi'iyyah, and Insaniyyah. The high and low quality of service can be determined by consumer behavior. The purpose is to determine how the quality of sharia-based services influences customer behavior. This research method is a cross-sectional design that is included in descriptive observation. The results showed that sharia-compliant pharmaceutical services positively impact customer satisfaction, as the significant value exceeds a t-value of 0.05. In conclusion, the quality of sharia-based services affects customer satisfaction.